Internal and External Dispersal of Plants by Animals: An Aquatic Perspective on Alien Interference - van Leeuwen, Casper H. A. (Frontiers in Plant Science, 2018)
Many alien plants use animal vectors for dispersal of their diaspores (zoochory). If alien plants interact with native disperser animals, this can interfere with animal-mediated dispersal of native diaspores. Interference by alien species is known for frugivorous animals dispersing fruits of terrestrial plants by ingestion, transport and egestion (endozoochory). However, less attention has been paid to possible interference of alien plants with dispersal of diaspores via external attachment (ectozoochory, epizoochory or exozoochory), interference in aquatic ecosystems, or positive effects of alien species on dispersal of native plants. This literature study addresses the following hypotheses: (1) alien plants may interfere with both internal and external animal-mediated dispersal of native diaspores; (2) interference also occurs in aquatic ecosystems; (3) interference of alien plants can have both negative and positive effects on native plants. The studied literature revealed that alien species can comprise large proportions of both internally and externally transported diaspores. Because animals have limited space for ingested and adhering diaspores, alien species affect both internal and external transport of native diaspores. Alien plant species also form large proportions of all dispersed diaspores in aquatic systems and interfere with dispersal of native aquatic plants. Alien interference can be either negative (e.g. through competition with native plants) or positive (e.g. increased abundance of native dispersers, changed disperser behavior or attracting additional disperser species). I propose many future research directions, because understanding whether alien plant species disrupt or facilitate animal-mediated dispersal of native plants is crucial for targeted conservation of invaded (aquatic) plant communities.